Intestinal Type of cystitis glandularis mimicking bladder tumor- case report and review of literature - Dr. Sukriti; Dr. Lavina Loungani; Dr. Prakash M. Roplekar; Dr. Snigdha Mukharji (Tropical Journal of Pathology and Microbiology, 2017)
Cystitis Glandularis of Intestinal type is an uncommon proliferative disorder with metaplastic alteration of the urothelium showing mucous secreting intestinal glands in the urinary bladder. An association of Adenocarcinoma with longstanding intestinal metaplasia of urothelium is controversial. Due to lack of this evidence and prognosis, we report a case of a 16-year-old male presenting with dysuria and a space occupying lesion in the bladder masquerading as a tumor mass. Cystoscopy revealed a well-circumscribed irregular nodal growth arising from the anterior wall of the bladder. Transurethral resection of the mass was performed and the histopathology suggested Cystitis Glandularis of Intestinal Type.